Statistical methods of computing reference values for side-to-side differences in nerve conduction studies. - Chang AS; Dillingham TR; Yu KF (American Journal of Physical Medicine & Rehabilitation)
This study uses theoretic derivations, statistical simulations, and empirical estimations to compare two ways of deriving reference values for side-to-side differences in nerve conduction parameters of healthy subjects. The two methods involve using the side-to-side differences (STSD) and the absolute values of the STSD (AVSTSD). The theoretic derivations showed that the population reference value of the AVSTSD is greater than the STSD reference values by 0.18%. Simulation studies showed that the AVSTSD yields greater sampling errors than the STSD method when establishing the reference values for nerve conduction parameters. However, the sampling variability is substantially reduced by using study samples of greater than 50, and the differences between the two methods in sampling errors are trivial as sample size approaches 100. Using H reflex (HR) and extensor digitorum brevis reflex (EDBR) clinical data, the two methods were compared. In contrast to the small theoretic differences in reference values, the AVSTSD method overestimated the reference value by 0.5 ms for the EDBR and 0.1 ms for the H reflex, when using data from a population sample, increasing the type II error (reducing sensitivity) for the EDBR. The STSD method is recommended for establishment of normal values and for clinical comparisons.